From descriptions to depictions: A dynamic sketch map drawing strategy. Issue 1 (2nd January 2016) - Kim, Junchul; Vasardani, Maria; Winter, Stephan
Abstract : People use verbal descriptions to communicate spatial information, externalising relevant parts of their mental spatial representations. In many situations, such as emergency response, the ability of a machine to interpret these verbal descriptions could assist in human-machine interaction. As a first step in such an endeavor, this paper presents an automatic approach that translates spatial objects and their spatial relations extracted from verbal descriptions via natural language processing into a plausible sketch map. The proposed methodology applies a hierarchical and dynamic sketch map drawing strategy that is inspired by heuristics people apply in their interpretation of place descriptions, in order to accommodate underspecifying, flexible and conflicting common language. The methodology is implemented and tested. This article ends with some insights for further research towards automatic interpretation of verbal place descriptions.